REPRESENTAÇÕES SOCIAIS DE PROFESSORES DO ENSINO BÁSICO SOBRE A INDISCIPLINA ESCOLAR - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
The themes of the research are the social representations of elementary school teachers on school indiscipline. Assuming that any social change implies a dialogue with the social representations of its actors, the main question of this research is: what are the characteristics of social representations of basic education teachers in state schools in Ponta Grossa-PR on indiscipline? The main goal of the research is pointing, through analytical reflection, characteristics of social representations of teachers of elementary and secondary schools in the city of Ponta Grossa-PR about indiscipline. These teachers' social representations are investigated by the theoretical and methodological framework of Social Representations Theory (Moscovici; Jodelet; Abric) and compared with the postulates on moral of Epistemology and Genetic Psychology (Piaget; Freitas). For the theoretical framework on school indiscipline we employed authors whose reading of this phenomenon starts from Epistemology and Genetic Psychology, such as La Taille, Parrat-Dayan Araújo and Pedro-Silva. It's a study of a multi-methodological nature (Camargo), which featured procedures in order to collect data and analysis of information. The procedures for data collection followed two phases: a questionnaire (N = 271) and semi-structured interviews (N = 40). The data collected were examined with the help of analysis programs, permeated by qualitative interpretation and hermeneutics of the researcher and supplemented by content analysis (Bardin). The research results indicated two fields on teaching social representation about the indiscipline. On one hand, a hegemonic social representation based on knowledge, attitude and heteronomy images in face of indiscipline, which attributes its motives to the students’ moral deficit caused by poor family education. It is a representation that absolves the teacher as a subject of indiscipline. On the other hand, some teachers share a representation which confers greater power to the elements of the pedagogic universe on the explanation of indiscipline. In here, knowledge, attitude and images pointed out are autonomous, such as comprehend and come closer to the student. I.e., we seek a horizontal relationship with the students, based on affection and social cooperation.
Social representations of elementary school teachers on school indiscipline. 2011-2013, 317 leaves
Keywords: indisciplina; representações sociais; autonomia; indiscipline; social representation; autonomy; CNPQ::CIENCIAS HUMANAS::EDUCACAO